PERBUATAN MELAWAN HUKUM ATAS PEMAKAIAN PERSEROAN TERBATAS (PT) YANG TELAH DIBALIK NAMAKAN DAN DIKUASAI TANPA SEPENGETAHUAN PERSERO LAINNYA - Rafael Valentino Rodja (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT That the Limited Liability Company Law as a basis for the establishment of PT also regulates the takeover procedure PT . In conjunction with the acquisition of PT were performed by non- shareholders and is in the PT , it can be said that an act against the law , because the certificate issued by the Notary legally flawed because it violates the Company Law No. 40 of 2007. That the legal consequences arising from a tort in civil perspective with respect to the acquisition of PT is not true is the compensation and may be subject to criminal penalties if viewed from the perspective of criminal law .Keywords : limited liability company , corporation, tort , behind the name .